EFFECTS OF REINFORCEMENT ON ATTITUDE OF GRATITUDE OF CHILDREN WITHIN AGES 4-7 YEARS IN ETCHE L.G.A. RIVERS STATE, NIGERIA - KENNEDY, Margaret G.; ASODIKE, Asodike (Journal of Professional Counselling, 2024)
The study examined the effects of reinforcement on attitude of gratitude among children of ages 4- 7 years. Observational method was used to assess attitude of gratitude before and after treatment. because of the potential inability of children aged 4-7 to provide responses to test questions. Two aims and two research questions guided the study. The population was made of 200 youngsters whose parents are members of the international recreation club at Shell Location Umuebulu11in Etche, Rivers State. Thirty-three children without attitude of gratitude were identified for the study and randomly placed into 2 groups. The observed group consists of 17 children who received treatment while the unobserved group of 16 were excluded from treatment. The method's validity was determined by comparing the level of agreement between the researchers at the same time. The approach's dependability was determined using Cohen Kappa's inter-observer agreement method. The effect of appreciation on the children was assessed before and after treatment, and compared with those in the unobserved group. The process consisted of three steps: introduction, consolidation, and termination. The results revealed a significant disparity in the level of consensus among observers between the group that was observed and the unobserved group. The findings demonstrated that the implementation of reinforcement had a significant impact on the treatment group. It was recommended that parents and teachers should be taught reinforcement tactics and should use them with children who lack a sense of appreciation.